The timing of maternal work and time with children - Jay Stewart (Institute for the Study of Labor (IZA), 2009)
I use data from the American Time Use Survey to examine how maternal employment affects when during the day that mothers of pre-school-age children spend doing enriching childcare and whether they adjust their schedules to spend time with their children at more-desirable times of day. I find that employed mothers shift enriching childcare time from workdays to nonwork days. On workdays, full-time employed parents shift enriching childcare time toward evenings, but there is little shifting among part-time employed mothers. I find no evidence that full-time employed mothers adjust their schedules to spent time with their children at more-preferred times of day, whereas part-time employed mothers shift employment to later in the day.
urn:nbn:de:101:1-20090619147
Keywords: J22; J13; 330; Timing of activities; time use; childcare; Frauenerwerbstätigkeit; Arbeitszeit; Kinderbetreuung; Mütter; Zeitbudgetforschung; USA